Robert Delpire : l’art d’un éditeur d’art - Annie Renonciat (Strenae)
This article offers insight into Robert Delpire’s career, examining possible connections made through his publishing activities, especially those which targeted a young audience. Promoting the image in its various forms, Robert Delpire worked as a photography and children’s picture book editor, advertising agency director, and art gallery founder; he was involved in film productions and exhibition creations, and headed the Centre National de la Photographie. His editorial production, with its stylistic diversity and originality, fostered in part by the creative outlet and income of his advertising work, places him in the tradition of "publisher-illustrators" alongside Léon Curmer, Pierre-Jules Hetzel and Paul Faucher.As with them, one finds not only an emphasis on the image, but a particular attention paid to the selection and promotion of artists (photographers, illustrators, and writers), as well as to the quality of graphics and page layout. As a children's books publisher, he can be compared to his predecessor Alfred Tolmer in particular, who, in a similar economic climate, also combined formal inventiveness with careful attention to detail in book production. Nevertheless, while Tolmer published children's books for his own personal amusement—a type of production that was not met with great literary approval—Robert Delpire viewed publishing as a full and distinct dimension within his role as an "image-showman."